Does the sizing of current cervical disc arthroplasty systems match Chinese cervical anatomic dimensions? - Wang, Lu; Bai, Meng; Li, Xing-Bin; Wang, Zhao-Rui; Wang, Bang; Huang, Ai-Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The objectives of this study were to analyze the computed tomography (CT) scan imaging data of the cervical spine from healthy volunteers and to correlate the measurements to the dimensions of current cervical disc arthroplasty systems. Methods: A total of 130 participants (78 males and 52 females) with a mean age of 41.0 years (range 18.0-66.0 years) who had undergone CT scans of the cervical spine were included. The linear parameters of the C3 to C7 levels, including anterior-posterior diameter (AP), middle disc height (DH), anterior disc height (ADH), posterior disc height (PDH) and center mediolateral diameter (ML), were measured. The analysis was conducted comparing different cervical levels, sexes, and age groups. Known dimensions from eight cervical disc arthroplasty systems were compared with the morphologic data. Results: A total of 520 vertebral segments were measured. The mean values for the measured parameters were as follows: AP 16.08±1.84 mm, ML 16.13±1.99 mm, ADH 3.88±1.11 mm, DH 5.73±1.00 mm, PDH 2.83±0.94 mm, and ML/AP 1.01±0.13. All parameters except for PDH were significantly different across the different cervical levels (P<0.05). There were also significant sex differences in terms of the linear parameters. No differences were found in the majority of parameters among the different age groups (P>0.05), except for AP at the C6/7 level. A comparison of the bone dimensions from the study data and the dimensions of the implants indicated the presence of a size mismatch in the currently available cervical disc prostheses. Conclusion: There is a large discrepancy between the cervical anatomical data of Chinese patients and the sizes of currently available prostheses. The dimensions collected in this study could be used to design and develop appropriate disc prostheses for Chinese patients.